Entrepreneurship in an Established Company - John Boden (Technology Innovation Management Review, 2009)
There are some fundamental differences between how you go about being innovative in a startup and how you go about it when you have more than 350 customers in 75 countries already running their business on your product. Put another way, you have to approach entrepreneurship differently when you have over 2,000 active deployments serving 40 million people every day. We faced that challenge at Movius Interactive Corporation. This article provides a description of how we took on the challenge of revitalizing innovation and entrepreneurship and how open source plays a part.